Multimedia-sequencing batch biofilm reactor in treating recycled paper mill effluent containing high level of pentachlorophenol: Long-term performance, mechanism and kinetic studies. (October 2020) - Muhamad, Mohd Hafizuddin; Abdullah, Siti Rozaimah Sheikh; Abu Hasan, Hassimi; Abu Bakar, Siti Nur Hatika
Graphical abstract: Highlights: Performance efficiency and process stability of MM-SBBR were influenced by different PCP load. High PCP, COD and NH3 -N removals were obtained during 600-day treatment period. The kinetic of PCP removal in MM-SBBR was best fitted to the Singh model. The adsorption capacity of GAC present in the MM-SBBR remained steady. Abstract: Discharging ill-treated wastewater from pulp and paper industry into water bodies causes accumulation of toxic and carcinogenic substances in the watercourse. A study on the removal of pentachlorophenol (PCP) from wastewater using a combination of granular activated carbon (GAC) adsorption and biofilm in multimedia-sequencing batch biofilm reactor (MM-SBBR) system was conducted. The performance, mechanism and kinetic of PCP removal were investigated using two lab-scale MM-SBBRs and three control bioreactors over a 600-day period. Both MM-SBBRs composed of Perspex column packed with plastic media filled with GAC were used with initial chemical oxygen demand (COD) of 1000 mg L −1 at a fixed hydraulic retention time (HRT) of 24 h. All five bioreactors working in parallel were spiked with different PCP concentrations (10 mg L −1, 50 mg L −1 and 100 mg L −1 ). MM-SBBR treating synthetic wastewater displayed the most effective PCP, COD and ammoniacal nitrogen (NH3 -N) removals ranging from 95 to 99 %, 93 to 99 % and 92 to 100 %, respectively. The kinetic of PCP removal in MM-SBBR system was best-fitted to Singh model ( R 2 > 88 %). The adsorption capacity of GAC present in the MM-SBBR bioreactor remained constant and thus, the adsorption mechanism played a key role in PCP removal. In conclusion, MM-SBBR system has potential for wastewater treatment in terms of performance efficiency and process stability, therefore, deserve a vote for pulp and paper mill effluents treatment.